Conductivity studies of grafted natural rubber and ionic liquid electrolyte systems - Rahmat, M.F.; Alias, Y.; Basirun, W.J.; Aldous, L.; Hardacre, C. (Malaysian Journal of Science, 2009)
Ionic liquids containing the 1-butyl-1-methylpyrrolidinium ([C4mPyrr]+) cation and bis(trifluoromethanesulfonyl)imide ([NTf2]-) anion have been synthesized and incorporated in 49% PMMA grafted natural rubber together with lithium salts to obtain solid polymer electrolytes (SPEs). The resultant SPEs obtained, are freestanding, flexible film and translucent and show conductivity over a wide range of 10-3-10-5 S cm-1. Polymer electrolytes containing 80% of (MG49:LiCF3SO3) and 20% of [C4mPyrr][NTf2] showed the highest conductivity of 2.11 x 10-3 S cm-1 at room temperature. The examination of the ionpolymer interactions and ionic conductivity are discussed and investigated by FT-IR and Electrochemical Impedance Spectroscopy (EIS) respectively.